The role of blood urea nitrogen to serum albumin ratio in the prediction of severity and 30‐day mortality in patients with COVID‐19. Issue 3 (6th May 2022) - Alirezaei, Toktam; Hooshmand, Saeede; Irilouzadian, Rana; Hajimoradi, Behzad; Montazeri, Sadra; Shayegh, Arash
Abstract: Background: Considering the role of higher blood urea nitrogen and lower serum albumin (SA) levels in deceased coronavirus disease 2019 (COVID‐19) patients, an increased blood urea nitrogen to SA (B/A) ratio may help to determine those at higher risk of critical illness. This study aimed to evaluate the correlation of the B/A ratio with severity and 30‐day mortality in COVID‐19 patients. Methods: A total of 433 adult patients with COVID‐19 were enrolled. The laboratory markers were measured on admission. Disease severity was categorized into mild disease, severe pneumonia, acute respiratory distress syndrome (ARDS), sepsis, and septic shock. The mortality was followed for 30 days after admission. χ 2 test, Fisher's exact test, and Mann–Whitney U test were performed, as appropriate. Also, logistic regression and the receiver operating characteristic (ROC) curve for the B/A ratio are included. Results: Thirty‐day mortality rate was 27.25%. The frequency of mild, severe pneumonia, ARDS, sepsis, and septic shock was 30.72%, 36.95%, 24.02%, 6.00%, and 2.31%, respectively. B/A ratio and SA levels were statistically different between alive and deceased patients. The mean B/A ratio was different among classified disease severities, except for mild disease. Logistic regression revealed the B/A ratio as an independent risk factor for sepsis after adjusting for age and sex. ROC analysis showed B/A ratio had an area under the curve (AUC) of 0.733 for mortality at the cutpoint of 4.944. AUC for sepsis was 0.617 which was greater than other disease severities. Conclusion: The results showed that B/A ratio and SA levels are associated with mortality of COVID‐19 patients. A higher B/A ratio is, additionally, associated with COVID‐19 severity, except in mild cases and it can act as an independent risk factor in sepsis. However, a greater B/A ratio is not a significant predictor of COVID‐19 severity, but it can predict mortality. Therefore, we suggest this marker for clinical assessment of patients with severe COVID‐19.